On the control of competitive balance in the major European football leagues - Ávila-Cano, Antonio Jesús; Triguero-Ruiz, Francisco Andrés (Wiley, 2022)
Authorities in the economic field (European Commission and US Federal Trade Commission) focus on the level of market concentration and establish limits in order to promote competition. However, sports authorities do not seem to pay the same attention to competitive balance in the national leagues, given the results achieved in the major leagues and limited interventions and regulations in this area. How are the major European football leagues evaluated based on the limits set for market concentration in the United States or the European Union? Following this line, we undertook a comparative analysis using the distance to competitive balance index, whose range is the unit interval, and define it as a function in a metric space. The comparative analysis shows, as in other studies, the high and ever-growing concentration of the results of these leagues over the past 25 years. With the European Commission and US Federal Trade Commission criteria, about one in three seasons would have been highly concentrated in the period analysed, and half in the last 10 seasons. Thus, it would seem reasonable that mechanisms that encourage competitiveness are considered.
Keywords: Economía; Fútbol; Equilibrio competitivo; Ligas de fútbol europeas